Sufisme Syekh Nawawi dalam Tafsir Marâh Labîd - Kholilurrahman Kholilurrahman (Al Aqidah (Jurnal Studi Islam), 2019)
This paper examines whether there are possibilities of the teachings of Sufism as outlined in the tafsir book Marâh Labîd, Is there a correlation of Sheikh Nawawi's notes in Salâlim al-Fudlalâ 'with the interpretation of Marâh Labîd? The results of this analysis conclude whether there is a interpretation of Marâh Labîd as a book of interpretations patterned as Sufism or not. The Sufi Sheikh Nawawi al-Bantani, a multi-disciplinary cleric as Sayyid ‘Ulamâ’ al-Hijâz and Sufism expert. He is a practitioner and writer. His phenomenal work is Salâlim al-Fudlalâ € ™ Syarh Hidayah Al-Adzkiyâ € 'whose entire writing is written with al-Sarraj in al-Luma' definition of Sufism teachings in the book Salâlim al-Fudlalâ '. Popular works, Nashâ-ih al-bIbâd Syarh al-Munabbiht ‘Alâ al-Isti’dâd li Yawm al-Ma'âd, contain pure Sufism to improve morals to Allah, His Messenger, and others. One of his great works, namely Marâh Labîd is known as Tafsir al-Nawawi or al-Munir al-Tafsir Li Ma’alim al-Tanzil.